The government and society of Penza region during the NEP - N.V. Semina; О.А. Sukhova (Известия высших учебных заведений. Поволжский регион: Гуманитарные науки)
Background. The actual importance of the chosen topic is determined by the need for a comprehensive study of various issues and forms of relations between the gov-ernment and society of the Russian province at the moments of fundamental historical changes, one of which was the period of implementation of the new economic policy, when all subsystems of society changed, the ideological attitudes of the population were trans-formed. Similar processes have been taking place quite recently: a change of ideas about the place and role of various social groups in Russian society, as the basis for newly formed moods. The purpose of the study is to comprehensively consider the problem of the rela-tionship between government and society during the NEP years based on the materials of the Penza province in order to find effective experience in the sustainable development of regions. Special attention is paid to the issues of interaction between the government and the population in solving the problem of homelessness and neglect, since the attitude to-wards minors determines the future development of any society. Materials and methods. The article uses various materials: archival, the results of research on the relationship be-tween government and the population in Russian historiography, legal sources (legislative and other official acts). Methodological approaches based on the principles of scientific consistency, objectivity, and historicism defined the subject of the study. Results. A com-prehensive study of the phenomena and facts of reality was based on an objective and im-partial interpretation and evaluation. The nature of the interaction between government and society in the period under study is analyzed. The problem of relations with the authorities in the Penza province in crisis socio-economic and political conditions is considered. The peculiarities of the perception of the population of the province of the events held by the authorities are reflected, contradictions in the relationship between the Penza public and the authorities are revealed, and the peculiarities of the existence of society in these historical conditions are reflected. The influence of state policy on relations within society and over-coming one of the most important problems – homelessness and neglect of children is stud-ied. Conclusions. Throughout the new economic policy, the relationship between society and government was contradictory. The problems in the implementation of the NEP direct-ly affected the relations between local party and state bodies and the Penza public. The cre-ation of the grassroots structures of the Soviet government was actually imposed on the peasantry as an entity hostile to the community. Volost and village councils acted in the field of administrative management, accounting and control, other issues were attributed to the powers of the assembly, which strengthened the countercultural nature of the Soviet government in relation to the community. In the second half of the 1920s, the new govern-ment absorbed the community, and the local structures of the Bolshevik Party possessed re-al fullness of power. Throughout the 1920s, there was an increase in social tension. The problem of homelessness and neglect of minors was acute. At the initial stage of the NEP, there were no well-coordinated institutions and actions aimed at overcoming the studied so-cial phenomena.